The Impact of Electronic and Conventional Cigarette Use towards Saliva Profile and Oral Microbiota in Adolescents - Kurniawan, Angelita Victoria; Amtha, Rahmi; Gunardi, Indrayadi; Heriandi, Alyah; Sari, Elizabeth Fitriana (Asian Pacific journal of cancer prevention : APJCP, 2025)
To compare the salivary profiles of smokers (e-cigarette smokers, e-cigarette and former conventional cigarette smokers, dual users, and conventional cigarette smokers) and non-smokers in adolescents, focusing on acidity level, flow rate, viscosity, as well as the quantity of Streptococcus mutans, Porphyromonas gingivalis, and Candida albicans. This analytical observational study, with a cross-sectional design, involves collecting saliva samples from five groups through the draining method. Saliva viscosity was assessed visually, while saliva flow rate was monitored over a ten-minute period. Quantification of bacterial presence was performed using qPCR, and salivary acidity was determined using a digital pH meter. Chi square and t-test were used to analyze the data. The total of 390 subjects (smokers n=195; non-smokers n=195), aged 17-25 years, participated in the study. Dual smokers exhibited a notable decrease in salivary pH (p=0.039) compared to non-smokers. Furthermore, significant reductions in flow rate (p<0.001) were observed across the five groups, however, no significant differences were found in saliva viscosity (p=0.070). When considering the four groups excluding conventional cigarette smokers, significant differences were observed in the quantity of Porphyromonas gingivalis (p=0.010) and Candida albicans (p=0.005). Conversely, the prevalence of Streptococcus mutans did not exhibit a significant difference (p=0.635). The study demonstrates that salivary pH, flow rate, and quantity of P. gingivalis as well as C. albicans are significantly different among the five groups.